Development of Problem-Based E-Modules on Environmental Change and Preservation to Improve Critical Thinking Skills of High School Students - Putri Nurrahma Maulida; Siti Alimah (Journal of Biology Education, 2026)
This study aims to determine the validity, feasibility, and effectiveness of problem-based Environmental Change & Preservation E-Modules as teaching materials to improve the critical thinking skills of high school students. This research uses the Research and Development (R&D) research type with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects in this study were students of class X SMA N 15 Semarang. The data collection methods used include interviews, validation questionnaires (media experts, materials, and teachers), student response questionnaires, and pretest-posttest questions. The results showed that the problem-based Environmental Change & Preservation E-Module product developed was valid, feasible, and effective in improving students' critical thinking skills with media expert validation results amounting to 96.25% with a very valid category, material expert validation results amounting to 91.25% with a very valid category, teacher validation results amounting to 100% with a very valid category, students gave a positive response, as well as the n-gain test results amounting to 0.58 in the medium category and the results of the Wilcoxon signed rank test with Asymp. Sig. (2-tailed) of 0.000 <0.05 which means there is a significant difference in the average pretest-posttest score. It can be concluded that the problem-based Environmental Change and Preservation E-Module is very valid, feasible, and effective to use in learning to improve the critical thinking skills of high school students.